RELEVANSI PEMIKIRAN AL-SYAIBANI ETIKA KERJA DAN PEMIKIRAN YAHYA BIN UMAR PENGAWASAN PASAR TERHADAP PRAKTIK UMKM MODERN DI KECAMATAN KADEMANGAN KOTA PROBOLINGGO - Diana Rizky Amalia (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research examines the relevance of Al-Syaibani's on work ethics and Yahya bin Umar's on market supervision against modern UMKM practices in Kademangan District, Probolinggo City. Using descriptive statistical analysis with Likert scale questionnaire instruments administered to 40 UMKM actors selected by purposive sampling, this study measures the alignment between classical Islamic economic principles and contemporary business practices. The results show that the work ethics dimension based on Al-Syaibani demonstrates a moderate relevance score with a mean of 3.12 (Moderate category), while the market supervision dimension based on Yahya bin Umar records a mean of 3.08 (Moderate category). Regression analysis indicates that these two dimensions collectively explain 64.7% of the variance in ethical UMKM practices. The findings confirm that classical Islamic economic thought remains highly relevant for modern UMKM development, particularly in strengthening work ethics and fair market mechanisms. These findings contribute to the development of Islamic economic theory and have practical implications for policy-making in UMKM empowerment.